The impact of Gender Diversity on Innovative Performance: Empirical Analysis in the Caribbean Region - Yury Castillo; Isabel Álvarez (Revista de Economía Mundial)
This paper investigates the impact of gender diversity on the innovative performance of Caribbean firms, specifically analyzing women’s representation across three organizational areas: the overall workforce, management, and skilled production and non-production roles. The study used data from the Innovation, Firm Productivity, and Gender (IFPG) database, encompassing 1,979 firms across 13 Caribbean countries from 2017 to 2020. Probit models were employed for econometric analysis. The results confirm that diversity significantly enhances the likelihood of innovation, though the magnitude of its impact varies depending on women’s roles within firms. Gender diversity has stronger effects within the overall workforce and skilled production and non-production roles than within management teams. These findings suggest important managerial and policy implications for developing measures to reduce gender disparities in innovation.